Strategi Optimalisasi Peningkatan Penjualan Melalui Sertifikasi Halal Pada UMKM Usaha Dodol Nanas CV Tulimario - Zilhikmah Safitri; Addiarrahman Addiarrahman; Erwin Saputra Siregar (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to describe the impact of changing CV Tulimario on the halal label of their products in Tangkit Baru Village, Sungai Gelam District, Muara Jambi Regency. Descriptive qualitative methods are used to analyze natural conditions and events in the field. Tangkit Baru Village has an area of ​​18,122 km² with a population of 2,974 people. CV Tulimario, founded by Mr H. Baso Intang in 1981, operates in the pineapple processing agro-industry sector, with main products such as pineapple dodol, pineapple chips and Nasgar drinks. This research found that CV Tulimario's sales strategy relies heavily on halal certification to increase competitiveness and consumer trust. Halal certification is considered important for market access in supermarkets and large stores, as well as improving consumer image and trust. However, the process of obtaining halal certification presents its own challenges, especially in meeting the requirements for suitability and cleanliness. This study emphasizes the importance of understanding market requirements and consumer needs, as well as commitment to hygiene and quality standards in production to support sustainable economic growth.